The Effect of Cognitive, Linguistic, and Social Factors in EFL Students’ Speaking Anxiety - Damayanti, Alfina; Cahyano, Bambang Yudi (Universitas Jambi, Magister Program of English Education Department, 2026)
Speaking anxiety is a persistent challenge for learners of English as a Foreign Language (EFL) and can significantly hinder their oral performance. This study investigates the influence of cognitive, linguistic, and social factors on EFL students’ speaking anxiety using a quantitative approach and Partial Least Squares Structural Equation Modelling (PLS-SEM). The participants consisted of 40 active students and alumni of the English Education Department at a well-known university in Indonesia. who had completed the Speaking course. Data were collected through a Likert-scale questionnaire adapted from the Foreign Language Classroom Anxiety Scale (FLCAS). The findings indicate that the linguistic factor has a significant positive effect on speaking anxiety, while cognitive and social factors do not significantly influence students’ anxiety levels. These results highlight that linguistic difficulties are the strongest contributors to speaking anxiety among the participants. Therefore, it is necessary to provide the students with learning strategies that can support the students' linguistic abilities, such as pronunciation practice, vocabulary improvement, and speaking activities.